Linguistic Exploration of the Word Laita in the Quran through Tafsir Fathul Qadir - Soleman, Soleman; Deski, Ahmad; Anwar, Efizal; Rambe, Irpan (El-Rusyd, 2026)
This research is motivated by the diversity of word usage in the Quran, which is not always understood in one meaning, but can show different meanings according to the context of the verse. Say has various linguistic functions, making it interesting to study through the interpretations of commentators. This study aims to classify the verses of the Quran that contain the word laita based on the subject who utters it, as well as analyzing the interpretation of the word laita in the Interpretation of Fathul Qadir. This research is content analysis, the method used is the interpretation method maudhu’i. The primary data source for this study is Imam Asy-Syauqani’s Tafsir Fathul Qadir and other secondary sources that can be used as supporting data. The results of the study indicate that the word laita in the Quran is mentioned 14 times. In terms of the subject who utters it, it can be classified into three groups: first, believers 2 verses; second, hypocrites 1 verse; and third, disbelievers 11 verses. Based on the analysis of interpretation in Tafsir Fathul Qadir, the use of the word laita shows variations in meaning influenced by the context of the sentence and the state of the subject who utters it. In relation to believers, laita means dreams and hopes that are difficult to realize. In hypocrites, laita means regret born from worldly interests. As for the unbelievers, laita means wishful thinking, hope, and regret after the truth is revealed and the coming of Allah SWT’s punishment. From all the data studied, the most dominant meaning is wishful thinking, especially wishful thinking about something that has passed or is impossible to come true again.